Experiential community health promotion: the UiTM ‘smile’ experience / Budi Aslinie Md Sabri ... [et al.] - Md Sabri, Budi Aslinie; Yusof, Norashikin; Md Bohari, Nor Faezah; Mohd Radzi, Nawwal Alawani; Md Yani, Azri Aliah; Nik Mohd Rosdy, Nik Mohd Mazuan; Hassan, Eddy Hasrul (2023)
Objectives: To increase the awareness of oral health professionals/public regarding new norms in oral health services delivery via mobile applications, website, and webinars via communication engagement learning.